(untitled) (UNED Research Journal, 2017)
This study aimed to investigate the diversity, intensity and prevalence of parasites in Cichlids. A total of 354 specimens of cichlids was sampled in polluted and unpolluted ends of Eleyele River, Ibadan, Nigeria and examined for parasites. The total prevalence was 57.34%. Recovered parasites were Clinostomum tilapiae, Euclinostomum heterostomum, Neascus, Allocreadium ghanensis, Phagicola longa, Alloglossidium corti and the acanthocephalan; Acanthogyrus tilapiae and Acanthella. Clinostomum tilapiae had higher prevalence and abundance (42.90%) with Allocreadium corti recording least abundance (0.49%). Tilapia zilli was the most abundant (41.53%) among the fish hosts but Oreochromis niloticus harboured the highest percentage of parasites (80.00%). The fish hosts in the polluted end of the river harboured the highest percentage of parasites (71.18%) against (43.50%) parasites recovered from the unpolluted end. There was a significant difference in the parasites harboured. Heavy infection with a broad number of parasites in fish hosts could reduce performance and productivity of the species, especially in fish farming.